2016
DOI: 10.1016/j.abb.2015.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic switch during adipogenesis: From branched chain amino acid catabolism to lipid synthesis

Abstract: Fat cell metabolism has an impact on body homeostasis and its proper function. Nevertheless, the knowledge about simultaneous metabolic processes, which occur during adipogenesis and in mature adipocytes, is limited. Identification of key metabolic events associated with fat cell metabolism could be beneficial in the field of novel drug development, drug repurposing, as well as for the discovery of patterns predicting obesity risk. The main objective of our work was to provide comprehensive characterization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 63 publications
2
57
0
1
Order By: Relevance
“…On the one hand, pyruvate can be transformed into acetyl CoA for citrate synthesis by the catalysis of PDH, 35 the expression of which was increased in PCTs. 38 Although additional in vitro or in vivo experiments were not performed to validate the functional consequence of our observed alterations, previous study revealed that altered BCAA metabolism drives cancer progression in myeloid leukaemia through the MSI2-BCAT1 axis. 49 It is noteworthy that the expression of BRP44 and BRP44L which encode the pyruvate transporters, was significantly elevated in PCTs, illustrating that enhanced pyruvate replenishment fuels the TCA cycle.…”
Section: Discussionmentioning
confidence: 87%
“…On the one hand, pyruvate can be transformed into acetyl CoA for citrate synthesis by the catalysis of PDH, 35 the expression of which was increased in PCTs. 38 Although additional in vitro or in vivo experiments were not performed to validate the functional consequence of our observed alterations, previous study revealed that altered BCAA metabolism drives cancer progression in myeloid leukaemia through the MSI2-BCAT1 axis. 49 It is noteworthy that the expression of BRP44 and BRP44L which encode the pyruvate transporters, was significantly elevated in PCTs, illustrating that enhanced pyruvate replenishment fuels the TCA cycle.…”
Section: Discussionmentioning
confidence: 87%
“…In accordance with our transcriptomic array data, both Hsp90β1 and Itgb7 were upregulated in PTLs compared to WT and GIT2KO thymus (Figure 4D, E: Tables S4, S5). A large proportion of this PTL-based dataset is strongly linked with metabolic aging and clock regulation [60, 61], cell senescence [62, 63] and age-related immune dysfunction [64] (Figure 4F). For each of the significantly-regulated PTL transcripts in these general categories (Figure 4F) it was evident that their regulation extent (z ratio magnitude) was consistently greater when compare to the dysfunctional GIT2KO thymus as opposed to the WT thymus.…”
Section: Resultsmentioning
confidence: 99%
“…HMGCS2 is one of the controlling enzymes in the mitochondrial mechanism of ketogenesis, an energy derivation process often entrained in the context of disrupted glucose metabolism and altered aging [49, 102]. HMGCS2 functionality is not only associated with ketogenesis but also with fatty acid β-oxidation, a compensatory process which is commonly observed in the context of disrupted aging mechanisms, age-related neurodegenerative conditions and age-related metabolic disruption [60, 78, 124]. Confirming our observations of disrupted Troma-I expression in the GIT2KO model it has also been demonstrated that reductions in Troma-I can also modulate HMGCS2 expression and in doing so modulate energy metabolism and ketogenic activity [103].…”
Section: Discussionmentioning
confidence: 99%
“…Examination of a 3T3-L1 adipocyte differentiation gene expression profile dataset [45] reveals dynamic changes in the levels of genes encoding LD-associated proteins (Fig. 2).…”
Section: Ld Enlargement In Brown White and Brite Adipocytesmentioning
confidence: 99%